1973
DOI: 10.1007/bf02531899
|View full text |Cite
|
Sign up to set email alerts
|

Role of luminal lecithin in intestinal fat absorption

Abstract: The effects of biliary lecithin on fat absorption were studied in 1 day bile fistula rats fed micellar solutions of bile salt, monoglyceride and radioactive free fatty acids. By electron microscopy and measurement of uptake of radioactivity into liver and adipose tissue, it was shown that in the absence of bile lecithin there was significant impairment of fat release from mucosa. Fat clearance was effected by the feeding of phosphatidyl choline or choline, but not phosphatidyl ethanolamine, inositol or cholest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 25 publications
8
57
0
Order By: Relevance
“…The unsuitability can be attributed to excessive fatty acids in the artificial feed, to excessive feeding facilitated by the consistency of the feed, which is abundantly provided, or to a deficiency in certain elements that are indispensable for the proper assimilation of lipids. For instance, it is well known that lecithins are important in the solubilization, absorption, and transport of fats in the mammalian intestine (O'Doherty et al 1973, Rodgers 1975, Tso et al 1977. One of lecithin components, choline, plays an essential role in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The unsuitability can be attributed to excessive fatty acids in the artificial feed, to excessive feeding facilitated by the consistency of the feed, which is abundantly provided, or to a deficiency in certain elements that are indispensable for the proper assimilation of lipids. For instance, it is well known that lecithins are important in the solubilization, absorption, and transport of fats in the mammalian intestine (O'Doherty et al 1973, Rodgers 1975, Tso et al 1977. One of lecithin components, choline, plays an essential role in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to see how this was possible with tolerable volume of test meal (not described in their paper) or without an alkaline pH (Hofmann, 1968), well buffered against gastric acidity. However, the output of absorbed lipid as chylomicrons in lymph was not measured in the present study nor in that of O'Doherty et al (1973). Experiments are underway using a steady state lymphatic absorption method (Shepherd and Simmonds, 1959) and a more stable test meal.…”
Section: Mucosal Recoveriesmentioning
confidence: 71%
“…Recently, O'Doherty, Kakis and Kuksis (1973) suggested that dietary or biliary lecithin play an important role in the normal transport of absorbed fat out of the intestinal mucosa. They found that mucosal content of absorbed radioactive fatty acid was decreased, whereas that of liver increased when egg lecithin was added to a gastric test meal of lipid and bile salts fed to bile fistula rats.…”
Section: Introductionmentioning
confidence: 99%
“…The major product of PC digestion, lysoPC, is water soluble and readily absorbed by enterocytes. It is a major source of enterocyte phospholipids for the generation of lipoproteins, and chylomicron formation as shown in the multidrug resistant Pglycoprotein knockout mice (23), for transport of triglyceride from the cell to lymph and for replenishment of membrane phospholipids used in exocytosis (12,13,24,25). Lack of cosecretion of PLA 2 could substantially impair these processes.…”
Section: Discussionmentioning
confidence: 99%